Economic factors that influence Malaysian export and import / Nurulhafizzah Aluai - Aluai, Nurulhafizzah (2007)
This study investigates the long-run relationship between economic factors and Malaysian exports and imports. Specifically, this study will determine the existence of relationship and also their predictive power (causality) between export and import. The variables used in this study are GDP, CPI, interest rate and exchange rate. Simply put, both the variables will converge towards equilibrium in long run which indicates the effectiveness of Malaysian's long term macroeconomic planning in stabilizing trade balance. The main objective of this study is to determine the long run relationship between economic growth and international trade (export and import). The other objectives of this research is to determine whether independence variables such as exchange rate, interest rate, gross domestic product (GDP) and consumer price index (CPl) has relationship with dependence variables such as export and import. The data for this study are collected from International Financial Statistics and annual reports of Bank Negara Malaysia for the period of 1997-2006. Towards this end, Multiple Linear Regression Model has been applied.